Optimalisasi Strategi Analisis Bisnis Melalui Perspektif Kajian Literatur - Sari, Yulianda (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to investigate the optimization of business analysis strategies through the perspective of literature review. By conducting a comprehensive literature review, this study seeks to gain a deep understanding of various business analysis strategies that have been examined in the literature. The discussions resulting from this research include identifying Challenges in Business Analysis and Refinement of Business Analysis Methods and Techniques. Additionally, in-depth discussions cover the Best Strategy Implementation in Organizational Contexts to Implications for business practices in Indonesia. Other findings highlight the importance of advanced information technology, such as big data analytics and machine learning, in enhancing the effectiveness of business analysis. In conclusion, this research concludes that by understanding and implementing business analysis strategies found in literature reviews, organizations can improve the quality of their decision-making, adapt their strategies to environmental changes, and achieve competitive advantages in the ever-changing market.